On the idealizing status of theoretical biology - Łastowski, Krzysztof (Anthropological Review, 1978)
The main thesis of the present article is the statement that among biological disciplines population genetics and evolutionism have reached the theoretical stage of development. Proof of this statement is provided by the idealized status of the Hardy-Weinberg rule and the Darwinian Theory of natural selection. The article also contains a historical analysis of discoveries preceding the theoretical shift in biology. This shift, in the author's opinion, is marked by the formulation of Mendelian Laws and ecoclimatic rules. In the light of historical analysis, the work of Charles Darwin and the emergence of population genetics is a transition from phenomenalistic induction to essentialistic idealization, from empirical to the theoretical stage of advancement of at least some of biological disciplines.